The carbonic acid industry; a comprehensive review of the manufacture and uses of CO₂. The commercial production of carbon dioxide. Design and construction of apparatus and machinery. Efficiency for refrigerating purposes. Mineral waters and other beverages. Methods of carbonating and bottling. Utilization of fermentation carbonic acid gas--its collection in the brewery. - Goosmann, Justus Christian, 1868- (Chicago, Nickerson & Collins Co., 1906)
Includes index. p. 357-368, advertising matter. Mode of access: Internet.